The mixed experiences of pregnant women with physical disabilities in accessing and utilising antenatal care services in rural south-western Uganda - Nuwagaba, Ponsiano Kabakyenga (Department of Health and Rehabilitation Sciences, 2023)
Background: In low- and middle-income countries, several environmental barriers impede accessibility to antenatal care (ANC) services for women with disabilities, yet ANC is a critical entry point for pregnant women to receive quality maternity care services. These barriers are more pronounced in rural areas than urban areas in Uganda. Although the World Health Organisation recommends that ANC services should be designed and continually improved based on locally generated data to address access barriers, the experiences of rural pregnant women with physical disabilities are largely undocumented. Aim: This study aimed to investigate the experiences of pregnant women with physical disabilities in accessing and utilising ANC services and suggest strategies for improving the services in rural south-western Uganda. Objectives: The study sought to: - describe the accessibility of ANC services - explain the utilisation of ANC services - explore the relationship between women with physical disabilities and health care providers - explore how women with physical disabilities and midwives understand disability and the provision of ANC services in rural south-western Uganda Methods: An interpretive qualitative study using a multiple case study design was conducted. Twelve women with physical disabilities and six midwives from three health facilities in Sheema district in south-western Uganda, East Africa, were selected as study participants. Women were sampled using snowball sampling. Midwives and health facilities (health centre III, health centre IV and general hospital) were sampled using purposive sampling. Data was gathered through in-depth face-to-face interviews with the women and midwives, a focus group discussion with the women, and direct observation of the physical environment at the three health facilities, from November 2020 to January 2021. Data was transcribed, translated, and thematically analysed with support of NVivo software. Ethical approval was obtained from University of Cape Town and Uganda National Council of Science and Technology, including a Risk Management Plan for preventing the transmission of Covid-19. Findings: Four themes were generated: 1. ‘Optimising wellbeing' was shaped by exercising agency, accessing family and community support, and aligning policy and practice. 2. ‘Undermining wellbeing' involved ignorance and mental ill-health (including emotional and spiritual oppression), sociocultural prohibitions, and inaccessible transport and mobility systems. 3. ‘Unresponsive ANC policy to women's specific needs' included the integrated nature of ANC services, unresponsive ANC policy, and unaccommodating health facility designs. 4. ‘Improving quality of ANC services' related to women's mixed experiences, preparing midwives and other health workers through education, training, and mentoring, and enabling disability inclusion for fit-for-purpose ANC services. Conclusion: Despite a few enablers optimising their wellbeing, rural pregnant women with physical disabilities experience many barriers that negatively impact on their pregnancy experiences and pregnancy health care. Women's spirituality is integral to their wellbeing. Justice, equity, and respect for their human dignity need to be underscored in ANC policy, health system and infrastructure planning, and midwifery education, training, and practice. The establishment of accessible quality ANC services within under-served areas benefits all women. The spirit of Ubuntu, which may facilitate women's participation and functioning at the family, community, and health facility levels, cannot be overemphasised. Going forward: An integrated framework for disability inclusive family- and communityfocused ANC services for rural communities is proposed. This framework needs to be tested to determine its efficacy in other rural African settings. A further study to explore the effectiveness of maternity waiting homes from the perspective of women with physical disabilities and the community in the context of rural Ugandan setting is suggested.